Educationalmanagement, democracy and citizenhip in times of pandemic Covid-19 (Revista Electrónica REDINE, 2021)
Living in democracy is not born from imposition, it is a collective construction made from the conviction that it is the best alternative that is built and strengthened in coexistence. Citizens are the driving force and guarantors of strengthening it by fully exercising their duties and rights through decision-making in public affairs. Consequently, it requires capacities and values ​​that have their main support in education. Therefore, in this essay we reflect on the educational management, democracy and citizenship the role that they have had to live in these difficult times when we face the tense particularities of the country in coexistence with the COVID-19 Pandemic. We maintain that our future and project as a nation is not thought from the rationality of progress and transcendence that education represent.
Keywords: Educational management; democracy; citizenship; pandemic